Blinatumomab use in pediatric B-ALL: where are we now? - Anurekha G. Hall; Rachel E. Rau (Blood Advances, 2025)
Abstract: Blinatumomab, a bispecific T-cell–engager antibody construct targeting CD19, has emerged as a transformative therapy in B-cell acute lymphoblastic leukemia (B-ALL) in both adult and pediatric populations. In pediatric populations, blinatumomab has demonstrated efficacy both in patients with relapsed or refractory disease and as a component of frontline therapy for newly diagnosed patients. In this review, we discuss the trials that led to regulatory approvals of blinatumomab, with an emphasis on its application in pediatric patients. We will also examine the use of blinatumomab in special populations, explore ongoing questions surrounding its role in the treatment of B-ALL, and highlight key considerations for future clinical use.